The effect of gadget use and self-control on academic procrastination - Dzikrillah, Viviana Salma Nur; Sari, Ratna (ARKA INSTITUTE, 2025)
This study aims to analyze the influence of gadget use and self-control on academic procrastination among university students. Using a quantitative approach with a non-experimental design, this research involved 75 students from the Faculty of Islamic Studies at Universitas Muhammadiyah Yogyakarta, selected through random sampling based on Slovin’s formula (10% margin of error). Data were collected through questionnaires measuring gadget use, self-control, and academic procrastination, then analyzed using multiple linear regression with SPSS. The results indicate that gadget use has a positive and significant impact on academic procrastination, while self-control has a significant negative effect. Together, these two variables contribute 82.1% to academic procrastination, with the remaining 17.9% influenced by other factors. These findings confirm that uncontrolled gadget use increases the tendency to procrastinate, whereas higher self-control minimizes this behavior. Therefore, effective strategies in managing gadget use and enhancing self-control are essential to reduce academic procrastination among students.